Faktor yang Mempengaruhi Permintaan Gigi Tiruan pada Lansia (Tinjauan Terhadap Biaya Perawatan, Kecemasan dan Sarana) - Fathul Rahman; Debby Saputera; Rosihan Adhani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2016)
Background: High rates of tooth extraction in Banjarbaru district without denture can reduce the esthetics and mastication function that affects the intake of nutrients, general health condition and quality of life. Purpose: The aim of this study is to know the factors that influnce demand for dentures on olderly of Tresna Werdha Budi Sejahtera Social Home in Banjarbaru. Methods: This is an observational analytic research with cross sectional design consist of 100 elderly with aged 60 years and over according to inclusion and exclusion category. Subjects ware asked to answer a questionnaire about demand denture and the factors that influence it. Data analysis using Chi Square and proceed with Contingency Coefficient. Results: Data analysis using Chi Square and proceed with Contingency Coefficient testshowed that the treatment cost factor have a significant association with denture demand (p<0.05) is equal (p = 0,014). Treatment cost was showed to be the most responsibility factor to anxiety factor and means for demand denture (C = 0.238). Conclusion: This research concludes that the most inhibiting demand denture factor in elderly of Tresna Werdha Budi Sejahtera Social Home in Banjarbaru is the cost of the treatment and manufacturing the denture are expensive.